An update to the Iberian spider checklist (Araneae) - Branco, Vasco Veiga; Morano, Eduardo; Cardoso, Pedro (Zootaxa, 2019)
We updated a previous database that compiled all the information available in 2010 for the species distribution of spiders (Araneae) in the Iberian Peninsula, Balearic Islands (Illes Balears) included. By the end of 2018 a total of 30834 records were compiled. These belong to 1493 species, 282 of those endemic to the peninsula, across 56 families and 402 genera. This represents an increase of approximately 14% in the number of species in the last nine years. From all families found in the Iberian Peninsula, Araneidae represent the highest number of records (3315), Linyphiidae the highest species richness (302) and Dysderidae the highest endemic richness (58). When considering only the 2010 decade, Linyphiidae lead in both number of records (1417) and species (49), but Gnaphosidae have the highest newly described endemic richness (18). When looking at the full data per province, the largest number of records are located in Illes Balears (1864), followed by Barcelona (1287). When it comes to species, Huesca (474) and Barcelona (470) are the richest provinces. However, it is Illes Balears that possesses the largest known endemic richness (43), followed by Beja and Faro (39). Regarding the last decade, Illes Balears received the largest sampling effort with 901 records, followed by Girona (806). Ciudad Real had the highest increase in known richness with 191 new species to the province, followed by León and Lleida (188). The most new endemic species were found in Faro (16), followed by Almería and Cádiz (13). This checklist is accompanied by an online catalogue where all its information is fully listed.